1H NMR Chemosensing of Potassium Ions Enabled by Guest‐Induced Selectivity Switch of a Gold Nanoparticle/Crown Ether Nanoreceptor. Issue 10 (5th April 2019) - Sun, Xiaohuan; Rosa‐Gastaldo, Daniele; De Biasi, Federico; Rastrelli, Federico; Mancin, Fabrizio
Abstract: A sensing protocol to detect potassium ions in water by 1 H NMR spectroscopy is described. The method exploits the K + ‐modulated affinity of 18‐crown‐6 functionalized gold nanoparticles towards organic ions, combined with NOE magnetization transfer. Binding of K + to the crown ether moieties switches the nanoreceptor preference (and its ability to transfer magnetization) from organic cations (tyramine) to organic anions (phloretate). In this way, a ratiometric NMR signal is produced with a detection limit of 0.6 mM. Detection can be performed in 20 min with standard instruments and with little interference from other alkali and alkaline earth metal ions present in the sample. Abstract : By NOE means : A sensing protocol to detect potassium ions in water by 1 H NMR spectroscopy exploits the K + ‐modulated affinity of 18‐crown‐6 functionalized gold nanoparticles towards organic ions, combined with NOE magnetization transfer. Binding of K + to the crown ether moieties switches the nanoreceptor preference from organic cations to organic anions. A ratiometric NMR signal is thus produced with a detection limit of 0.6 mM. Other ions, organic molecules and even proteins present in the sample produce little interference.